Sodium Intake and Nutritional Status Hypertension Patients In Hative Passo Hospital - Sammeng, Wahyuni; Castanya, Meiske Sylvia; Marsaoly, Michran; Ruaida, Nilfar (Media Publikasi Cendekia Indonesia, 2022)
Hypertension is the result of measuring systolic blood pressure of more than 140 mmHg and diastolic blood pressure of more than 90 mmHg carried out twice with an interval of five minutes in a calm state with provisions for someone aged ≥ 18 years. Nutritional status is one of the factors that can increase a person's risk of hypertension. Someone who is overweight tends to experience hypertension because being overweight will affect a person's physiology, namely insulin resistance and hyperinsulinemia. The purpose of this study was to determine sodium intake and nutritional status in hypertensive patients at Hative Hospital, Passo. This research method is quantitative using a descriptive approach with a sample of 8 people. The number of outpatient visits of hypertensive patients without complications during May at the hospital was only 8 people. Data collection used a research instrument in the form of a semi-quantitative food frequency questionnaire (FFQ-SQ), as well as determining nutritional status by measuring body mass index (BMI). Data analysis technique using univariate analysis. Sodium intake of patients is categorized as grade I hypertension which is recommended for 3 (100%), grade II hypertension is recommended for 3 people (75%), 1 person (25%) is not recommended and grade III hypertension is not recommended 1 person (100%). Patients often consumed junk food with high sodium, resulting in an increase in blood volume and nutritional status caused by calorie intake, lack of physical activity, and other disease disorders